Nómina de producción y sus inconvenientes en el pago del impuesto a la renta en la empresa Bananito. - Japon Chaunay, Wilman Arturo (2018)
One of the priorities of the National Government of Ecuador is to increase the revenues of the General State Budget in order to achieve and achieve a high level of public spending the same as demand for social and productive investment, which will contribute to economic growth and as well as the reduction of poverty. It is vital to be able to determine the causes, circumstances and estimate the tax evasion in the province of El Oro because this way it will be possible to know in a quantitative way the damage caused to the State, it will also serve to measure the efficiency of the Tax Administration regarding the control of taxpayers. Tax evasion is considered as an illegal behavior which is done by taxpayers, whether in a culpable or fraudulent manner, which amounts to omission. Failure to pay taxes will result in the theft of payment of those obligations. same that are tributary, which have their beginning in a valid way in the life of the right, this occurs when information is hidden from the tax administration. The income tax is presented from the income that is obtained from natural persons, the companies are foreign or national and the undivided estates. The income tax corresponds from January 1 to December 31 of each year, depending on the results of the economic activity of each person; even when all the income comes to be constituted by income that is exempt. The tax system is very important in each state because it will be able to manage the taxes or taxes which are contributed by the taxpayers, these taxes come to serve to maintain public spending. The tax evasion is presented as a fact of great concern in all countries of the world, due to the effects that come to produce among these the decline in income that has the state, as well as the decrease in private investment, through a bibliographic study could be known as countries get to lose millions of dollars due to tax evasion, for this measures must be taken so that this can be completed and for this evasion must be measured so that in this way the tax administration can improve tax control, taxes tend to differentiate from taxes because employees can help with their benefits, without getting any benefit which is not approved or supported by law. For this reason, it was necessary to carry out the present work through a bibliographical study since through the scientific articles it has been possible to determine what are the causes that some authors present so that there is no tax awareness and the production payroll does not exist. make the payments of your income taxes, this coming to affect the state.